Upper limb static-stretching protocol decreases maximal concentric jump performance - Marchetti, P. H.; de Oliveira Silva, F. H. D.; Soares, E. G.; Serpa, E. P.; Nardi, P. S. M.; Vilela, G. de B.; Behm, D. G. (Journal of Sports Science & Medicine, 2014)
The purpose of the present study was to evaluate the acute effects of an upper limb static-stretching (SS) protocol on the maximal concentric jump performance. We recruited 25 young healthy, male, resistance trained individuals (stretched group, n = 15 and control group, n = 10) in this study. The randomized between group experimental protocol consisted of a three trials of maximal concentric jump task, before and after a SS of the upper limb. Vertical ground reaction forces (vGRF) and surface electromyography (sEMG) of both gastrocnemius lateralis (GL) and vastus lateralis (VL) were acquired. An extensive SS was employed consisting of ten stretches of 30 seconds, with 15 seconds of rest, and 70-90% of the point of discomfort (POD). ANOVA (2x2) (group x condition) was used for shoulder joint range of motion (ROM), vGRF and sEMG. A significant interaction for passive ROM of the shoulder joint revealed significant increases between pre- and post-SS protocol (p < 0.001). A significant interaction demonstrated decreased peak force and an increased peak propulsion duration between pre- and post-stretching only for stretch group (p = 0.021, and p = 0.024, respectively. There was a significant main effect between groups (stretch and control) for peak force for control group (p = 0.045). Regarding sEMG variables, there were no significant differences between groups (control versus stretched) or condition (pre-stretching versus post-stretching) for the peak amplitude of RMS and IEMG for both muscles (VL and GL). In conclusion, an acute extensive SS can increase the shoulder ROM, and negatively affect both the propulsion duration and peak force of the maximal concentric jump, without providing significant changes in muscle activation.